فعالية الخرائط الذهنية في تعليم النحو في المدرسة الثانوية - Aprilianti, Dian; Arifin, Syamsul; Alawiyah, N. Lalah (Kalimatuna: Journal of Arabic Research, 2023)
This research aims to reveal the implementation of nahwu learning by using mind mapping and the effectiveness of mind mapping in nahwu learning. This research is a quantitative research that uses a quasi-experimental method. The data collection techniques used are tests, interviews, and observations. In analyzing the data, the researcher used the t-test formula. After processing and analyzing the data, the researcher got the results of t-count 3,796 and t-table 2,371 and 1,667, which means t-count is bigger than t-table. Then H0 is rejected and Ha is accepted. From these results it can be concluded that the use of mind mapping in nahwu learning is effective. This shows that the use of mind mapping can be applied in nahwu learning.